Salivary total protein as a biomarker of anaerobic threshold in elderly athletes subjected to an incremental physical test - Justino, Allisson B.; Neto, Anibal MM; Bortolini, Miguel J. S.; Peixoto, Leonardo G.; Prado, Eduardo S.; Garcia-Hortal, Marina; Botelho, Françoise V.; Espindola, Foued S. (Biology of Sport, 2018)
This study aimed to verify whether salivary total protein (STP) would reflect anaerobic threshold in elderly athletes subjected to an incremental exercise test. Methods: Seven elderly elite athletes (EEA) and six physically active elderly men (PAE) completed a treadmill protocol in which blood and saliva samples were collected. Results: Blood lactate (BL) and STP increased significantly in EEA during the test (0.8 ± 0.2 to 5.1 ± 2.0 mmol/L and 42.5 ± 7.5 to 222.5 ± 63.8 mg/dL, respectively) and remained elevated at five minutes after exercise (5.0 ± 1.9 mmol/L and 147.2 ± 50.0 mg/dL, respectively). Furthermore, correlations between STP and heart rate (r = 0.87, p < 0.001), and between BL and STP (r = 0.96, p < 0.001), were observed in the elderly athletes. Conclusions: STP represents a potential non invasive biomarker for determining anaerobic threshold during an incremental exercise test, and this parameter may be used as an indicator of physical exercise intensity in elderly athletes.